Effective intravenous delivery of adenovirus armed with TNFα and IL-2 improves anti-PD-1 checkpoint blockade in non-small cell lung cancer - Tatiana V. Kudling; James H.A. Clubb; Santeri Pakola; Dafne C.A. Quixabeira; Iris A.K. Lähdeniemi; Camilla Heiniö; Victor Arias; Riikka Havunen; Victor Cervera-Carrascon; Joao M. Santos; Eva Sutinen; Jari Räsänen; et al. (OncoImmunology)
Lung cancer remains among the most difficult-to-treat malignancies and is the leading cause of cancer-related deaths worldwide. The introduction of targeted therapies and checkpoint inhibitors has improved treatment outcomes; however, most patients with advanced-stage non-small cell lung cancer (NSCLC) eventually fail these therapies. Therefore, there is a major unmet clinical need for checkpoint refractory/resistant NSCLC. Here, we tested the combination of aPD-1 and adenovirus armed with TNFα and IL-2 (Ad5-CMV-mTNFα/mIL-2) in an immunocompetent murine NSCLC model. Moreover, although local delivery has been standard for virotherapy, treatment was administered intravenously to facilitate clinical translation and putative routine use. We showed that treatment of tumor-bearing animals with aPD-1 in combination with intravenously injected armed adenovirus significantly decreased cancer growth, even in the presence of neutralizing antibodies. We observed an increased frequency of cytotoxic tumor-infiltrating lymphocytes, including tumor-specific cells. Combination treatment led to a decreased percentage of immunosuppressive tumor-associated macrophages and an improvement in dendritic cell maturation. Moreover, we observed expansion of the tumor-specific memory T cell compartment in secondary lymphoid organs in the group that received aPD-1 with the virus. However, although the non-replicative Ad5-CMV-mTNFα/mIL-2 virus allows high transgene expression in the murine model, it does not fully reflect the clinical outcome in humans. Thus, we complemented our findings using NSCLC ex vivo models fully permissive for the TNFα and IL-2- armed oncolytic adenovirus TILT-123. Overall, our data demonstrate the ability of systemically administered adenovirus armed with TNFα and IL-2 to potentiate the anti-tumor efficacy of aPD-1 and warrant further investigation in clinical trials.